2015
DOI: 10.1370/afm.1736
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Chronic Abdominal Pain Affecting the Well-Being of Children in Primary Care

Abstract: PURPOSE Abdominal pain is a frequent symptom among children but is rarely associated with organic disease. Although it may persist for years, no factors have been identified that predict its prognosis. Our aim was to determine whether patient characteristics at initial consultation can predict chronic abdominal pain severe enough to influence the child's well-being at 1 year of follow-up. METHODSWe conducted this prospective cohort study in primary care, including consecutive children aged 4 to 17 years seen f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
4
14
0
Order By: Relevance
“…These numbers are higher than the prevalence of chronic pain in the German epidemiological sample, which reported a prevalence rate of 33% based on the same chronic pain definition (Häuser, Schmutzer, Hinz, Hilbert, & Brähler, ). However, in line with a Dutch study on recurrent abdominal pain (Spee et al, ), our results indicate that parental pain is not a risk factor for treatment failure in a child receiving primary care due to medically unexplained pain. While it is known that parental cognitions and behaviour have significant impact on a child’s pain experience (Feinstein et al, ; Poppert Cordts, Stone, Beveridge, Wilson, & Noel, ), these cognitions and behaviour may not be necessarily associated with parental chronic pain.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These numbers are higher than the prevalence of chronic pain in the German epidemiological sample, which reported a prevalence rate of 33% based on the same chronic pain definition (Häuser, Schmutzer, Hinz, Hilbert, & Brähler, ). However, in line with a Dutch study on recurrent abdominal pain (Spee et al, ), our results indicate that parental pain is not a risk factor for treatment failure in a child receiving primary care due to medically unexplained pain. While it is known that parental cognitions and behaviour have significant impact on a child’s pain experience (Feinstein et al, ; Poppert Cordts, Stone, Beveridge, Wilson, & Noel, ), these cognitions and behaviour may not be necessarily associated with parental chronic pain.…”
Section: Discussionsupporting
confidence: 91%
“…Demographic characteristics were not predictive. This is partially in line with results from the Dutch primary care study of children with recurrent abdominal pain (Spee et al, ), in which sex was not associated with treatment outcome, but older children were more likely to have ongoing pain. In our study, no child with a migration background visiting a doctor for the first time due to pain developed disabling chronic pain.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…A recent study found that more than onethird of children with recurrent abdominal pain continued to complain of pain 1 year after starting treatment. 13 More than 40 years earlier, Apley and Hale 14 reported that one-third of children with recurrent abdominal pain continued to experience symptoms into adolescence. The comparison of outcomes from these 2 studies performed 4 decades apart is disheartening.…”
mentioning
confidence: 99%